2010
DOI: 10.1510/icvts.2009.227967
|View full text |Cite
|
Sign up to set email alerts
|

Onset of peripheral arterial disease: role of endothelin in endothelial dysfunction☆

Abstract: Plasma concentrations of ET in patients with PAD are greatest in early disease; ET concentrations decrease substantially and inflammation arises as disease advances. Serum CRP concentrations exhibit a modest negative correlation with those of ET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The endothelin receptor antagonists (bosentan and ambrisentan) have been approved for use in pulmonary arterial hypertension (PAH) and have been assigned orphan drug status. Details of hepatotoxicity of bosentan, ambrisentan, and sitaxentan are reviewed in de Haro Miralles et al ( 2010 ). Endothelin-1 is a powerful endogenous vasoconstrictor (Frumkin, 2012 ) and thus blocking endothelin could improve perfusion to the lower extremities in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelin receptor antagonists (bosentan and ambrisentan) have been approved for use in pulmonary arterial hypertension (PAH) and have been assigned orphan drug status. Details of hepatotoxicity of bosentan, ambrisentan, and sitaxentan are reviewed in de Haro Miralles et al ( 2010 ). Endothelin-1 is a powerful endogenous vasoconstrictor (Frumkin, 2012 ) and thus blocking endothelin could improve perfusion to the lower extremities in patients with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…In a pre-clinical PAD model, Luyt et al ( 2000 ) demonstrated that endothelin, antagonists, bosentan, and darusentan (LU13525) increased tissue blood flow measured by laser Doppler perfusion imaging. de Haro Miralles et al ( 2010 ) examined plasma levels of endothelin and showed that endothelin levels were increased in patients with intermittent claudication compared to non-PAD controls. Just as importantly patients with the most severe form of PAD, CLI, did not demonstrate elevated levels of endothelin, which suggests that an elevation of endothelin is specific to the pathophysiology of intermittent claudication and not all forms of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated circulating levels of ET-1 have been repeatedly observed in scleroderma, as well as in various other pathologies in which the vascular endothelium is involved [22]. It has been also detected an increase in plasma levels of ET-1 in situations of acute or chronic limb ischemia, chronic and acute coronary syndromes, acute renal failure, and stroke [23,24]. Nevertheless, the role of ET-1 activity as a causal factor of endothelial dysfunction and/or damage or an epiphenomenon remains not completely clear [22,25].…”
Section: Effect Of Bosentan On Microcirculation Physiopathologymentioning
confidence: 98%
“…Several studies have shown that can improve endothelial function after 4 weeks of treatment, indirectly demonstrated by the increasing of the flow-mediated dilation (FMD) measurements in the brachial artery in patients with systemic sclerosis, diabetes mellitus, microalbuminuria, and peripheral artery disease [17,24,30].…”
Section: Effect Of Bosentan On Microcirculation Physiopathologymentioning
confidence: 99%
“…In addition to their beneficial effects on NO bioavailability, statins have also been shown to affect circulating levels of numerous other vasoactive peptides produced by the endothelium. Endothelin-1 (ET-1) is a potent vasoconstrictor implicated in the pathophysiology of PAD (59,60) and has been shown in a recent meta-analysis of 15 RCTs to be significantly lowered following statin use (weighted mean difference of -0.30 pg/ml) when compared to placebo (61). This decrease is thought to be related to the down-regulation of prepro-endothelin-1 mRNA via Rho protein-associated pathways (62,63), and is maintained even in the presence of ox-LDL (62).…”
Section: Seminal Work By Laufs and Colleagues Supported This Hypothesmentioning
confidence: 99%